The bacteriocin Angicin interferes with bacterial membrane integrity through interaction with the mannose phosphotransferase system - Vogel, Verena; Olari, Lia-Raluca; Jachmann, Marie; Reich, Sebastian J.; Häring, Michelle; Kissmann, Ann-Kathrin; Rosenau, Frank; Riedel, Christian U.; Münch, Jan; Spellerberg, Barbara (Frontiers in Microbiology, 2022)
In a natural environment, bacteria are members of multispecies communities. To compete with rival species, bacteria produce antimicrobial peptides, called bacteriocins. Bacteriocins are small, cationic, ribosomally synthesized peptides, which normally inhibit closely related species of the producing organism. Bacteriocin production is best studied in lactic bacteria (LAB). Streptococcus anginosus, belonging to LAB, produces the potent bacteriocin Angicin, which shows inhibitory activity against other streptococci, Listeria monocytogenes and vancomycin resistant Enterococcus faecium. Furthermore, Angicin shows a high resistance towards pH changes and heat, rendering it an interesting candidate for food preservation or clinical applications. Here, we demonstrated by liposome leakage and pHluorin assays that Angicin destroys membrane integrity. The inhibitory activity of Angicin depends on the presence of a mannose phosphotransferase system in target cells, since L. monocytogenes harboring a deletion in an extracellular loop of this system are no longer sensitive to Angicin. Furthermore, we demonstrate the low cytotoxicity against human cell lines and liposomes derived from eucaryotic membranes. In conclusion, we demonstrate that Angicin has a detrimental effect on the membrane of target organisms and uses the Man-PTS as a receptor.